HLA Class I and Class II Polymorphisms and Anti-nuclear Antibodies in Hyperprolactinaemic Iraqi Females with Primary Infertility - Ad'hiah, Ali H.; Al-Tmemi, Manal B.; Hussain, Sabah M.; yaseen, Nahi Y. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The study was conducted to investigate the association between hyperprolactinaemia and markers of human leukocyte antigen (HLA) system in a sample of Iraqi infertile females, together with the profile anti-nuclear antibodies (ANA). Objectives: One hundred and seventy five female patients (age range: 20 -40 years) were recruited in this study. They were attending the Institute for Embryo Research and Infertility Treatment (Al-Nahrain University) during the period January 2005 - September 2006. Results:After clinical and laboratry evaluations, it was found that 100 patients were hyperprolactinaemic, whereas the other 75 patients were euprolactinaemic, therefore, they were considered as a control group. Based on serum level of prolactin (22-29, 30-39 and ≥ 40 ng/ml), the total hyperprolactinaemic patients were divided into three groups; I (35 patients), II (40 patients) and III (25 patients), respectively. The HLA antigens showed significant variations between patients (total and groups) and controls. In total patients, B8 (25.0 vs. 9.3%), DR3 (48.0 vs. 17.3%) and DR4 (39.0 vs. 13.3%) showed significant increased frequencies, while B35 showed a significant decreased frequency (7.0 vs. 24%). The latter decrease was also observed (5.7 vs. 24.0%) in group I of patients, which also showed a significant increased frequency of DR3 (54.3 vs. 17.3%). In groups II and III of patients, only DR3 (45.0 and 56.0, respectively vs. 17.3%) and DR4 (37.5 and 56.0, respectively vs. 13.3%) showed significant increased frequencies. Autoantibody evaluation by ANA test revealed that 22% of the total patients was positive, while all control subjects were negative, and such positivity paralleled the increased level of serum prolactin.